Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1097/00007890-199908270-00015
|View full text |Cite
|
Sign up to set email alerts
|

Poor Outcome in Patients With Diabetes Mellitus Undergoing Liver Transplantation.

Abstract: Poorer outcome in the diabetics undergoing OLT, particularly in those with ALD, suggests the need for a more detailed pre-OLT assessment of these patients, particularly those with insulin and tablet controlled diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 4 publications
7
64
0
1
Order By: Relevance
“…Post-OLT survival of liver transplant recipients with DM had been reported to be less than the survival of those without DM in 1 series, 13 but the rest of the series reported to date did not find significant differences. 12,14-17 Our patients with DM had greater survival and it was even greater in those who required pharmacological treatment to achieve metabolic control.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Post-OLT survival of liver transplant recipients with DM had been reported to be less than the survival of those without DM in 1 series, 13 but the rest of the series reported to date did not find significant differences. 12,14-17 Our patients with DM had greater survival and it was even greater in those who required pharmacological treatment to achieve metabolic control.…”
Section: Discussionmentioning
confidence: 87%
“…[12][13][14][15][16][17] In 1 study, 13 liver transplant recipients with DM had a lower survival rate than those without DM. Conversely, other studies did not show a difference between patients with and without DM.…”
mentioning
confidence: 99%
“…[13][14][15][16][17] In a more recent investigation, the prevalence of diabetes in cirrhotic patients was 53%, as defined by formal glucose tolerance testing. 18 The reason for the 3-fold variability in the earlier series is not clear.…”
Section: Prevalence Of Diabetes In Liver Transplant Recipientsmentioning
confidence: 99%
“…These optimistic results were not observed in three other studies. 14,15,17 In one of these studies, 15 the death rate among diabetics was 4-fold greater than among matched nondiabetic liver recipients; insulin-dependent diabetics fared worse than those controlled by diet alone. Patients with alcoholic liver disease and insulintreated diabetes fared worst of all, and hepatitis C was more prevalent in the diabetics than the nondiabetics.…”
Section: Impact Of Diabetes On the Outcome Of Liver Transplantationmentioning
confidence: 99%
“…Despite the lack of universal agreement, some studies have observed worsened short-and mid-term survival among diabetic LT recipients. [1][2][3][4][5][6][7] Furthermore, DM is a wellknown risk factor for cardiovascular disease, which is one of the leading causes of death of LT recipients in the long term. 8 Calcineurin inhibitors (CI) also predispose to DM through islet cell toxicity, diminished insulin synthesis or release, as well as decreased peripheral insulin sensitivity.…”
Section: D Abetes Mellitus (Dm)mentioning
confidence: 99%